Using the most significant change (MSC) technique to evaluate the vasectomy program in Tagum City, Philippines - Pellano, Seneca N.
In this study, I sought to gain understanding about conducting program evaluation with communication at its core. This was actualized by testing the usefulness and/or applicability of a participatory evaluation approach, known as the Most Significant Change (MSC) technique, in evaluating the vasectomy program in Tagum City, Philippines. Qualitative design was used as process of inquiry in this study. It has three components: (1) the story collection done by Barangay Health Workers (BHWs), which constitute the first step in conducting MSC; (2) the Focus Group Discussion (FGD) involving BHWs and City Health Officers to allow the vasectomy program stakeholders to experience the MSC selection process; and (3) the generation of suggested refinements from all stakeholders which served as feedback about the MSC process. Analysis of stakeholders' MSC experience revealed that the MSC process was found useful in evaluating Tagum City's vasectomy Program. The MSC technique was found effective in facilitating empowerment through shared understanding and enabling learning by different stakeholders involved in the program. It also enabled them to deliberate, clarify, and understand matters related to the program's impact. However, factors such as muting voices and weaknesses of the diary method appeared to limit the applicability and usefulness of the MSC process in this study. To address these limitations, suggested refinements of the MSC process were recommended.